Investigate the Relationship Between Self-Care, Health Literacy and Social Support in Patients with Hypertension Referring to the Specialized Heart Clinic of Tohid Hospital in Sanandaj - Rozhin Bahmani; Nazila Olyaie; sonia darvishi; Neda Sheikhakaryaee (Hamadan University of Medical Sciences, 2021)
Background and Objective: Self-care in hypertension is one of the most significant strategies in order to control the disease; moreover, health literacy and social support are regarded as effective factors in this case. Therefore, considering the necessity and need of society in promoting the level of health literacy and social support, as well as the role and importance of self-care in hypertension, the aim of the present study was to determine the relationship among self-care behavior and health literacy and social support in patients suffering from hypertension. Material and Methods: The descriptive-analytical study was cross-sectional and was conducted on 400 patients with hypertension referring to the specialized heart clinic of Tohid Hospital in Sanandaj, Iran, using the convenience sampling method. The Four-part Demographic Questionnaire, the Self-Care Behavior Assessment Questionnaire, the Health Literacy for Iranian Adults Questionnaire and Social Support Questionnaire were used so as to collect the data. To analyze the data, SPSS software version 21 and parametric tests of Pearson correlation coefficient and non-parametric Kruskal-Wallis analysis were used. Results: The findings indicated that mean and standard deviation of Self-Care Behavior Score and Health Literacy and Social Support were 38/64 ± 8/83, 63/10 ± 11/16 and 91/54 ± 6/93, respectively. There was a Positive significant relationship between Self-Care Behavior and Health Literacy (r=0/491, P=0/00), Self-Care Behavior and Social Support (r=0/322, P=0/00), Social Support and Health Literacy (r=0/337, P=0/00). Conclusion: The results of the present study showed that having health literacy and social support would influence the individual and the occurrence of self-care behaviors, and since these cases are highly effective in preventing and controlling hypertension, it is necessary to train and promote them in the health system.